Legal Protection For Users Of Air Cargo Transportation Services (Study At PT. Anugerah Semesta Persada) - Rio Peranata Sebayang (Institute Of computer Science (IOCS), 2020)
Implementation of the rights and obligations of users of cargo transportation services, PT. Anugerah Semesta Persada (EMPU) and airlines are included in the expedition agreement where the agreement is a reciprocal agreement between the forwarder and the sender, and the forwarder binds himself to find a good carrier for the sender, while the sender binds himself to pay fees. to the forwarder. This expedition agreement is included in the air transportation agreement so that it must comply with the Law of the Republic of Indonesia Number 1 of 2009 concerning Aviation. The method used in this paper is normative research, namely research conducted by examining library materials related to the problem to be studied. Library materials used as sources of research are obtained from books, articles, papers, magazines, and electronic media such as the internet. The case study was conducted at the PT. Anugerah Semesta Persada (EMPU) is a company that operates as an expediter under the leadership of SUHENDRA and REKAN in order to complete the data in completing the research. The conclusion shows that the implementation of the rights and obligations of users of cargo transportation services, PT. Anugerah Semesta Persada (EMPU), and airlines are included in the expedition agreement where the agreement is a reciprocal agreement between the forwarder and the sender, and the forwarder binds himself to find a good carrier for the sender, while the sender binds himself to pay fees. to the forwarder. The aircraft used in this transportation are passenger aircraft. Carriage using checked baggage on passenger aircraft. Baggage must not exceed capacity so as not to endanger flight safety. The responsibility of PT. Anugerah Semesta Persada and airline companies in carrying out cargo transportation by aircraft are lost in whole or in part, when damaged, and late arriving at the destination. This expedition agreement is included in the air transportation agreement so that it must be subject to the Law of the Republic of Indonesia Number 1 of 2009 concerning Aviation. Implementation of legal protection for users of aircraft cargo transportation services at PT. Anugerah Semesta Persada is regulated in the Decree of the Minister of Transportation No. KM 77 of 2011 concerning Responsibilities of Air Transport Carriers.